Dinamika Interaksi Sosial Masyarakat Austria di Tengah Perkembangan Budaya dan Pariwisata: Studi Kasus Kota Vienna - Hezrinavanya; Albert Januar Christian; Rino Adibowo; Christian, Albert (Global Political Studies Journal, 2025)
This study analyzes how social interactions in Austrian society have been transformed by the rapid development of Vienna’s culture and urban dynamics. As a complex city, Vienna brings together local and foreign residents who engage in diverse social, economic, and cultural activities. One major driver of this transformation is globalization, along with the increasing number of tourists, which influences communication patterns, lifestyles, and social values. The research employs a qualitative approach using analytical descriptive methods. Data were collected from relevant literature, particularly Austrian government reports, publications from international organizations such as UNESCO and the OECD, and supporting academic studies. The findings indicate that Viennese society demonstrates a high level of tolerance and adaptability in response to global influences and international engagement. Nevertheless, traditional Austrian values such as order, politeness, and social solidarity remain central to social life. The study argues that Vienna’s hospitality and tourism industry, including accommodation services, functions not only as an economic sector but also as a key arena for shaping and strengthening social interactions. With its global impact, Vienna illustrates how a city can bridge macroeconomic prosperity, social well-being, and cultural preservation. Keywords— Austrian Society, Culture, Social Interaction, Tourism, Vienna